2018
DOI: 10.3390/ijerph15112526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Application of a Program of Adapted Utilitarian Judo (JUA) on the Fear of Falling Syndrome (FOF) for the Health Sustainability of the Elderly Population

Abstract: This research analyzes the fall history of a group of elderly people and studies the effects of an intervention program based on Adapted Utilitarian Judo (JUA) to teach fall control in subjects with fear of falling syndrome (FOF). We adopted a quasi-experimental research design with pre-post measurement of the experimental group, in a healthy, pre-fragile sample of 12 women aged 71.5 ± 8 years, chosen using non-probabilistic-incidental accessibility sampling. The WHO questionnaire was used for the functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 26 publications
(31 reference statements)
4
49
0
2
Order By: Relevance
“…The results obtained with respect to our intervention, in terms of reducing the fear of falling, are consistent with those of Halvarsson, Olsson, Farén, Pettersson, and Ståhle [29]; Logghe et al [30]; Parraca et al [24]; Li, Fisher, Harmer, and McAuley [21]; Brouwer et al [31]; Barnett et al [32]; Dueñas et al [33]; Sattin et al [34] (much larger in the tai chi group than in the education for well-being); Huang [35]; and Toronjo et al [10]. In all of the studies cited, the fear of falling was reduced and they concluded that the interventions were effective.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results obtained with respect to our intervention, in terms of reducing the fear of falling, are consistent with those of Halvarsson, Olsson, Farén, Pettersson, and Ståhle [29]; Logghe et al [30]; Parraca et al [24]; Li, Fisher, Harmer, and McAuley [21]; Brouwer et al [31]; Barnett et al [32]; Dueñas et al [33]; Sattin et al [34] (much larger in the tai chi group than in the education for well-being); Huang [35]; and Toronjo et al [10]. In all of the studies cited, the fear of falling was reduced and they concluded that the interventions were effective.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies were based on vibration training [25], as well as on the improvement of balance and flexibility [26][27][28]. However, regarding research like the present study in which AUJ is implemented to reduce the fear of falling, we only found the one conducted by Toronjo et al [10].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Con respecto a la variable del miedo a caer, el STAC, medido a través del FES-I, observamos que nuestro sujeto obtiene una mejora de 5 puntos tras la intervención, obteniendo como puntuación inicial 27 puntos y fi nal 22 puntos. Situándonos en el estudio de Toronjo-Hornillo (28), donde se establece tres niveles de clasifi cación para este cuestionario, siendo de 16 a 19 puntos, un nivel bajo de miedo a caer, de 20 a 27 puntos un nivel moderado, y de 28 a 64 puntos, un nivel alto, esta puntuación indica que el sujeto empezó la intervención presentando un grado moderadoalto de miedo a caer, mientras que tras la intervención, ha conseguido que su miedo a caer sea moderado.…”
Section: Discusión Y Conclusionesunclassified
“…Por otro lado, cuando nos planteamos conocer cómo infl uye la aplicación del JUA en la salud de nuestro sujeto de estudio, tras analizar los resultados obtenidos en el SF-36, observamos que esta intervención ha infl uido positivamente en el estado de salud de nuestro sujeto, 2022;11(2): 1-14 principalmente en la dimensión de salud mental, que es el grado de depresión, ansiedad, control de la conducta y bienestar general del sujeto (28).…”
Section: Discusión Y Conclusionesunclassified